Aluminum oxide/polydimethylsiloxane-based Q-switched mode-locked erbium-doped fiber laser - Mohd Yusoff, N.; Abdul Hadi, M.A.W.; Zainol Abidin, N.H.; Alresheedi, M.T.; Goh, C. S.; Mahdi, M.A. (Elsevier, 2022)
A Q-switched mode-locked (QSML) erbium-doped fiber laser integrating aluminum oxide saturable absorber (Al2O3-SA) is demonstrated. With the help of polydimethylsiloxane polymer, Al2O3 powder was securely transferred on a tapered fiber surface and functioned as SA. A QSML pulse sequence was realized at a central wavelength of 1567.4 nm from 80 to 320 mW pump power with its envelope repetition rate ranging from 30.59 to 77.46 kHz. The short duration of 2.54 µs Q-switched envelope comprised of 8.3 ns ML pulses with 252 nJ pulse energy was realized at the maximum pump power of 320 mW. The high damage threshold of Al2O3-SA of beyond 7 GW/cm2 contributes to the future exploration of bulk metal oxide for high-energy optical pulse generation in near-infrared wavelengths.